2011
DOI: 10.1080/0951192x.2011.554872
|View full text |Cite
|
Sign up to set email alerts
|

Power assessment as a high-level partner selection criterion for new product development projects

Abstract: International audienceIn New Product Development (NPD) projects, various partners may be involved at different phases and their participation can lead to either success or failure of the project. Therefore, a company that launches a NPD project has to carefully select the most appropriate partners. Currently, partner selection in supply chains is often performed according to well-known criteria such as cost or delay. However, problems could emerge in such processes due to the unavoidable power disequilibrium o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Understanding the relative power towards a supplier is particularly important in cases when the supplier is new and the interaction is planned over an extended period of time. With established suppliers, power might become a means for leverage in contract or price negotiations [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the relative power towards a supplier is particularly important in cases when the supplier is new and the interaction is planned over an extended period of time. With established suppliers, power might become a means for leverage in contract or price negotiations [14].…”
Section: Discussionmentioning
confidence: 99%
“…Being able to apply pressure upon weaker actors means that the stronger partner has been able to understand its real source of power and was able to use it. However, if a company overestimates or underestimates its own power, its consequent actions could affect its ability to negotiate successful collaboration with the supplier or customer and reduce its agility [14]. The role of power is crucial to its interactions with other relationship structures; power can seriously affect the level of confidence and commitment between parties [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, all three case organizations were aware of the importance of having knowledgeable employees to conduct the user development initiative; but not all of them have a formal procedure for the selection process. Prior research has mainly focused on the importance of having supplier assessment in order to increase new product development projects (Zolghadri et al, 2012) and supply chain agility (Ngai et al, 2011). No studies were found in the literature concerning user development.…”
Section: Discussionmentioning
confidence: 99%
“…The most suitable option within MADM is AHP, which is used extensively in supplier selection [59,[120][121][122]. This method is a good method for our research because unlike the other MADM methods mentioned above, it accommodates the subjective values, including the decision maker's preferences.…”
Section: Optimisationmentioning
confidence: 99%